External iliac artery injury with posterior pelvic ring injury in Korea: two case reports - Joosuk Ahn; Ji Wan Kim (Journal of Trauma and Injury)
Pelvic ring injuries associated with external iliac artery injuries are rare and may be life-threatening condition. The most important factors in the managements are the immediate bleeding control and restoration of distal blood flow. We report two cases of pelvic ring injuries with external artery injuries. One case was occlusion of external iliac artery with concomitant rupture of internal iliac artery. The other case was ruptured external iliac artery. Every surgeon must understand the possibility of hidden lesions—for example, arterial rupture and thrombus—and should consider the need for embolization or thrombectomy when treating this type of injury.